Pengaruh Video Tutorial Terhadap Penguasaan Teknik Dasar Sepak Bola Siswa SMP Negeri 1 Gerung - Jalaluddin El Rumi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the effect of using video tutorials on the mastery of basic soccer techniques among students at SMP Negeri 1 Gerung. The basic techniques examined include dribbling, passing, shooting, and ball control. The research method employed was a quasi-experimental design with a pretest-posttest control group format. The research sample consisted of 60 students who were randomly divided into two groups: the experimental group, which used video tutorials as a learning medium, and the control group, which applied conventional methods without media assistance. Data were collected through observation and skill tests on basic soccer techniques that had been validated by experts. The results of data analysis using the t-test revealed a significant difference between the posttest mean scores of the two groups. The experimental group demonstrated a greater improvement in mastering basic soccer techniques compared to the control group. This finding indicates that the use of video tutorials has a positive impact on improving students’ understanding and practical skills in soccer techniques. In addition, video tutorials were considered effective in enhancing learning motivation and accelerating the learning process, as they provide clear visualizations of movements that can be replayed according to students’ needs. Therefore, video tutorials can serve as an innovative alternative learning medium in physical education.